Bile Imprint on Parietal Peritoneum of Gilthead Seabream and Red Seabream: Effects of Fasting Duration, Stress, and Ice Storage - Sofia Brinkmann Bougali; Nafsika Karakatsouli; Christos Balaskas; Konstantinos Petropoulos; Despoina Trampouli; Alkisti Batzina; Pinelopi-Paraskevi Laskari (Fishes)
The Mediterranean aquaculture industry has recently been confronted with the appearance of a bile imprint on fish filets, which to-date remains of unknown etiology. This study investigates the involvement of common procedures applied before (fasting), during (confinement), and after (ice storage) fish harvesting. Two experiments were designed, one for gilthead seabream (Sparus aurata) and one for red seabream (Pagrus major). The fish were grouped according to fasting duration (1, 2, 3 days), harvesting method (stressed, unstressed), and ice storage (0 h, 48 h). In both species, the imprint appeared in all ice-stored fish for 48 h but not in fresh fish (0 h), the color of the imprint became darker as Days of Fasting increased, stressed fish had darker imprints than unstressed fish, and plasma and bile osmolality and cholesterol were significantly affected by treatments. The histological examination of the gallbladder in red seabream showed great variability in the muscularis thickness and appearance, regardless of treatment. These results are not conclusive as to the cause of the bile imprint appearance. However, they offer a first insight into an issue that bears significant impact in the marketing of aquaculture products and may foster further investigation in the search of the underlying causes of this reoccurring issue.